2012
DOI: 10.1371/journal.pone.0049446
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Suppressive CD8 T Regulatory Cells Are Increased in Patients with Multiple Myeloma: A Cause for Immune Impairment

Abstract: BackgroundMultiple myeloma (MM) is a plasma cell malignancy frequently associated with impaired immune cell numbers and functions. In MM, several studies have previously shown that CD4 regulatory T (Treg) cells hamper effector T cell functions and enhance immune dysfunction. In this study, we aimed to prove the presence of functionally suppressive Treg cells expressing CD8 phenotype (CD8 Treg cells) in MM. To the best of our knowledge, this has not been reported previously in MM.MethodsWe analyzed CD8 Treg cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
(40 reference statements)
2
34
0
Order By: Relevance
“…We were the first to demonstrate that the amount of CD8 + Tregs is significantly increased in MM patients as compared with healthy subjects. Similar to CD4 + Tregs, CD8 + Tregs expressed elevated levels of FOXP3, cytotoxic T lymphocyte antigen-4 (CTLA4) and CD62L, while exhibiting a CD127 −/dim+ phenotype 5 . RT-PCR data confirmed the deregulation of CD8 + Tregs in MM patients, clearly showing that these cells express higher levels of FOXP3 than their normal counterparts 5 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We were the first to demonstrate that the amount of CD8 + Tregs is significantly increased in MM patients as compared with healthy subjects. Similar to CD4 + Tregs, CD8 + Tregs expressed elevated levels of FOXP3, cytotoxic T lymphocyte antigen-4 (CTLA4) and CD62L, while exhibiting a CD127 −/dim+ phenotype 5 . RT-PCR data confirmed the deregulation of CD8 + Tregs in MM patients, clearly showing that these cells express higher levels of FOXP3 than their normal counterparts 5 .…”
mentioning
confidence: 75%
“…Similar to CD4 + Tregs, CD8 + Tregs expressed elevated levels of FOXP3, cytotoxic T lymphocyte antigen-4 (CTLA4) and CD62L, while exhibiting a CD127 −/dim+ phenotype 5 . RT-PCR data confirmed the deregulation of CD8 + Tregs in MM patients, clearly showing that these cells express higher levels of FOXP3 than their normal counterparts 5 . Functional assays revealed that CD8 + Tregs isolated from both MM patients and healthy individuals inhibit the proliferation of CD4 + T cells as well as their ability to secrete IFNγ (but not interleukin-10, IL-10) in a concentration-dependent manner.…”
mentioning
confidence: 99%
“…Recently, a regulatory subset of CD8 + T-cells has been identified in myeloma patients, with the ability to suppress CD4 + T-cell proliferation via the secretion of IFN-γ [84]. The clinical role of this subset of T-cells is currently unknown, although they are believed to contribute to immune suppression in myeloma.…”
Section: The Impact Of Hematopoietic Derived Cells On Myeloma Progresmentioning
confidence: 99%
“…There is also circumstantial evidence suggesting that CD8 T cells may be able to block the MGUS-to-MM progression during tumor development as long as the incipient myeloma cells maintain sufficient antigen-presentation capability to cytotoxic CD8 T cells [127]. On the minus side, a report on a significant increase in the number of suppressive CD8 T cells in MM suggests that these cells may in fact contribute to both the local immune suppression in the TME and the systemic immune deficiency commonly seen in patients with myeloma [128]…”
Section: Figmentioning
confidence: 99%